The Effect of Providing Local Plant-Based Herbal Drinks on Glycemic Control in Type 2 Diabetes Mellitus Patients in Tanah Merah Village, Badar District, Southeast Aceh Regency - Herlitawati Herlitawati; Rohani Rohani; Devi Susanti; Taufik Hidayat (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2026)
Type 2 Diabetes Mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin secretion and insulin resistance. The increasing prevalence of Type 2 DM is influenced by unhealthy lifestyles, lack of physical activity, and changes in people's dietary patterns. One effort to control blood sugar levels is the use of local herbal plants as complementary therapy. This study aims to analyze the effect of providing herbal drinks based on local plants on glycemic control in patients with Type 2 DM in Tanah Merah Village, Badar District, Southeast Aceh Regency. This study used a quantitative method with a quasi-experimental design through a one-group pretest-posttest design. A sample of 60 respondents was selected using a purposive sampling technique. Data collection was carried out by examining blood glucose levels before and after administering the herbal drink based on local plants using a glucometer. Data analysis used a paired t-test with a significance level of 0.05.α= 0.05. The results of the study showed that the average blood glucose level before giving herbal drinks was 238.6 mg/dL and after the intervention decreased to 187.3 mg/dL. The results of the statistical test obtained a p-value = 0.000 (p < 0.05), indicating that there was a significant effect of giving local plant-based herbal drinks on glycemic control in Type 2 DM patients. A decrease in blood glucose levels of 51.3 mg/dL indicates that local plant-based herbal drinks have the potential to help control blood sugar levels in Type 2 Diabetes Mellitus patients. The results of this study are expected to be a source of information for the public and health workers regarding the use of local herbal plants as complementary therapy in controlling Type 2 Diabetes Mellitus.